Greenland 1979 microwave remote sensing data catalog report, October 14 and 15, 1979 - Hennigar, Harold F.; United States. National Aeronautics and Space Administration. Scientific and Technical Information Branch. (Washington, D.C. : National Aeronautics and Space Administration, Scientific and Technical Information Branch, 1983)
"March 1983"--Cover. Includes bibliographical references. Mode of access: Internet.